STUDENT’S PERSPECTIVES TOWARD A-AIKEM 3 MODEL IN GROUP WORK PRESENTATION - Henry Rio Putranto (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2019)
As there is a tendency to regard that a classroom without the label of cooperative learning is not a good one, recent instructional practices then often utilize group work to encourage students to gain knowledge from one another – to assist and to seek assistance from their peers in addition to from the classroom teacher. Classrooms have the typical characteristics of small groups. With the trend to incorporate cooperative learning in the classroom practices, this Positive Interdependence is undoubtedly to be imposed to obtain the beneficial outcomes of cooperative efforts.This research would like to employ a new model in group work presentation called A-aikem 3. This A-aikem 3 model is an innovative group work presentation model which emphasizes on CL approach. This model can be used to strengthen positive interdependence, individual accountability, interpersonal and also group processing skill from students. Basically,A-aikem 3 model is one of many A-aikem models formulated and designed by Tamah and Prijambodo on their book. The A-aikem 3 model developed based on three new insights that are (1) transition from individual (conventional) assessments to group assessment, (2) transition from individual assessment to peer assessment , and (3) transition from Individual assessment without discussion to a representative assessment with discussion. (Tamah & Prijambodo, 2015 in Tamah, 2017) Deriving from the title of this thesis and the background of the study, two relevant research questions are formulated as follows: How do the undergraduate students perceive A-aikem 3 model? What are the positive and negative feedbacks of A-aikem 3 model’? In relation to the research questions above, this study aims to investigate the student’s perspective towards A-aikem 3 model and also their feedback after experiencing A-aikem 3 model.